Efficiency Improvement of Ground-Mounted Solar Power Generation in Agrivoltaic System by Cultivation of Bok Choy (Brassica rapa subsp. chinensis L.) Under the Panels - Kumpanalaisatit, Manoch; Setthapun, Worajit; Sintuya, Hathaitip; Jansri, Surachai Narrat (International Journal of Renewable Energy Development, 2022)
An agrivoltaic system is a combination of solar power generation and crop production that has the potential to increase the value of land. The system was carried out at a 25-kW photovoltaic (PV) power plant located at the Asian Development College for Community Economy and Technology (adiCET), Chiang Mai Rajabhat University, Thailand. The growth and yield of bok choy (Brassica rapa subsp. chinensis L.) and the solar power output were investigated and compared with the control. Moreover, the efficiency of the agrivoltaic system was evaluated. The results indicated that the average intensity of solar radiation of 569 W/m2 was obtained. The highest power generation was recorded in the PV with crop production of 2.28 kW. Furthermore, the control plot of crop production at 35 days provided higher growth than bok choy plots under solar panels of 2.1 cm in plant height, 6 in leaf number, 2.2 cm in leaf length and 0.2 cm in leaf wide. High-yield of bok choy was also obtained in the control plot of 17.31 kg. Although the yield of bok choy is extremely low, possibly because of light intensity, crop cultivation under solar panels could reduce the module temperature to less than the PV control of 0.18 Â°C, resulting in increased voltage and power generation by around 0.09 %. Therefore, an agrivoltaic system is another option for increasing revenue and land equivalent ratio in solar power plants focusing only on electricity generation. However, suitable crops for the space under PV panels should be investigated further.